Medical androgen deprivation therapy and increased non-cancer mortality in non-metastatic prostate cancer patients aged ≥66 years. Issue 11 (November 2015) - Abdollah, F.; Sammon, J.D.; Reznor, G.; Sood, A.; Schmid, M.; Klett, D.E.; Sun, M.; Aizer, A.A.; Choueiri, T.K.; Hu, J.C.; Kim, S.P.; Kibel, A.S.; et al.
Abstract: Purpose: To examine the potential relationship between androgen deprivation therapy and other-cause mortality (OCM) in patients with prostate cancer treated with medical primary-androgen deprivation therapy, prostatectomy, or radiation. Methods: A total of 137, 524 patients with non-metastatic PCa treated between 1995 and 2009 within the Surveillance Epidemiology and End Results Medicare-linked database were included. Cox-regression analysis tested the association of ADT with OCM. A 40-item comorbidity score was used for adjustment. Results: Overall, 9.3% of patients harbored stage III–IV disease, and 57.7% of patients received ADT. The mean duration of ADT exposure was 22.9 months (median: 9.1; IQR: 2.8–31.5). Mean and median follow-up were 66.9, and 60.4 months, respectively. At 10 years, overall-OCM rate was 36.5%; it was 30.6% in patients treated without ADT vs. 40.1% in patients treated with ADT (p < 0.001). In multivariable-analysis, ADT was associated with an increased risk of OCM (Hazard-ratio [HR]: 1.11, 95% Confidence-interval [95% CI]: 1.08–1.13). Patients with no comorbidity (10-year OCM excess risk: 9%) were more subject to harm from ADT than patients with high comorbidity (10-year OCM excess risk: 4.7%). Conclusions: In patients with PCa, treatment with medical ADT may increase the risk of mortality due to causes other than PCa. Whether this is a simple association or a cause–effect relationship is unknown and warrants further study in prospective studies.